Environmental Impacts Management of the Coachella Valley Music and Arts Festival - Anindya Kenyo Larasti (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2019)
The sustainability of music festivals is an urgent issue that must be discussed. Without careful consideration of environmental impacts, the short-term economic gain becomes a long-term fiasco. Coachella, the second-largest music festival in the US and the highest-grossing festival in the world, is possible to harm the environment. It provides pressure by bringing a hundred thousands of people at the same time and place. If the festival damages the environment, it will be costly and taking a long time to preserve the ecosystem. Therefore, it is crucial to assess the management of environmental impacts to recognise how a music festival could increase its environmental sustainability. The analysis ascertained qualitatively by using an approach of energy usage, waste generated, and transport emission produced (Fredline et al., 2005).The result shows that much work has been done by Coachella organisers to reduce the environmental impact of the music festival they organised. First, the energy used in Coachella does not have too much impact on the environment because Coachella has applied sustainable energy framework. Next, in term of waste management, Coachella has been trying to minimise waste generated during the event by organising a massive waste sorting program. It can be said that the program has been quite successful at managing waste. Last, emissions produced from transport have the worst impact on the environment because it directly contributes to climate change. Furthermore, the organisers cannot control the number of vehicles used by attendees because this subject is at the preference of each attendee, and the organiser cannot fully control it.